2008
DOI: 10.3201/eid1403.070128
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-ResistantAcinetobacter baumanniiOsteomyelitis from Iraq

Abstract: Multidrug-Resistant Acinetobacter baumannii Osteomyelitis from Iraq

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…Another study revealed Gram-negative rods like A. baumannii were widely present in first episodes of osteomyelitis but more rarely present in recurrences or treatment failures despite drug resistance and orthopaedic devices [21]. In two case reports of patients with A. baumannii, osteomyelitis resolved uneventfully with débridement and 6 weeks of antibiotics [17,20]. These findings are consistent with low or reduced virulence of A. baumannii, as suggested by our experiments.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Another study revealed Gram-negative rods like A. baumannii were widely present in first episodes of osteomyelitis but more rarely present in recurrences or treatment failures despite drug resistance and orthopaedic devices [21]. In two case reports of patients with A. baumannii, osteomyelitis resolved uneventfully with débridement and 6 weeks of antibiotics [17,20]. These findings are consistent with low or reduced virulence of A. baumannii, as suggested by our experiments.…”
Section: Discussionsupporting
confidence: 90%
“…The literature supports a limited role for A. baumannii in clinical osteomyelitis [8,17,20,21]. In one study, clinical improvement of osteomyelitis, including MDR AB, occurred without recurrence in 18 of 18 patients after a mean of 9 months, often despite the presence of internal stabilization and lack of extended continuation therapy with oral antibiotics.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding bone infection specifically, animal studies have in fact indicated high eradication rates of susceptible bacteria in osseous tissue when tigecycline is locally implanted (Kaya et al, 2012) or systemically administered (Kandemir et al, 2008). Two case reports in humans have further documented success in treating osteomyelitis due to a resistant Klebsiella isolate (Chen et al, 2010) and a multidrug-resistant Acinetobacter species (Schafer & Mangino, 2008), respectively, while another has suggested the efficacy of tigecycline and colistin employed concomitantly to combat a bone infection caused by a resistant Pseudomonas aeruginosa (Stanzani et al, 2007). Finally, a case series of six patients has elucidated favorable outcomes in S. epidermidis osteomyelitis (Asseray et al, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…In one report, it was the most frequently found Gram negative isolate from war wounds [10]. Isolated cases of Acinetobacter osteomyelitis were also reported: (1) an 8-year-old boy after hamster bite, treated with parenteral dual antimicrobial therapy (gentamicin and carbenecillin) for 6 weeks [11], (2) a previously injured patient from an armory fragment, causing an open fracture of right femur and treated with parenteral monotherapy (gentamicin) for 6 weeks [12], and (3) a 55-year-old soldier injured by a grenade with osteomyelitis of left proximal femur, treated with parenteral monotherapy (tigecycline) for 43 days [13]. The largest case series reported is by Davis et al on 23 soldiers wounded in Iraq war who had wound cultures positive for MDR Acinetobacter species [14].…”
Section: Discussionmentioning
confidence: 99%